Gardens of the Iberian Peninsula New perspectives on an entangled history - Horsch, Nadja; Scholz-Hänsel, Michael; Oliveira Sonius, Marta (Kulturen - Kommunikation - Kontakte, 2023)
In garden research, Spanish and Portuguese green spaces are scarcely visible. This is a striking contrast not only to their diversity and quality but also to the global network of both countries, especially during the Early Modern period. To counterbalance this, specialists from Spain, Portugal and Germany gathered in 2021 on an international and interdisciplinary conference. In the Portuguese Palace of Queluz they discussed the fundamental issues of garden art on the Iberian Peninsula. Their contributions are collected in this book. They are proof of a cross-border transcultural approach, which has freed itself from national stereotypes. Also, it addresses insights which have been derived from the cultural interaction across the centuries and the different epochs of garden art.